COMPETENCE DEVELOPMENT OF COUNSELING GUIDANCE (BK) TEACHERS AS OPTIMIZATION OF GUIDANCE SERVICES AND COUNSELING IN THE SOCIETY ERA 5.0 - Tiara Maiza Dianti; Neviyarni; Firman (Yayasan Citra Dharma Cindekia, 2022)
This article discusses the development of BK teacher competencies as an effort to optimize guidance and counseling services in the era of society 5.0. Using references from relevant literature studies, this article discusses competencies that are in accordance with national education standards. There are four competencies that must be possessed by a teacher/educator, namely pedagogic, personality, social and professional competencies so that later teachers/educators can carry out their duties and responsibilities as an educator well and can face changes in the era of society 5.0 because the progress of the world of education cannot be separated from the role of educators for the importance of developing the competence of educators.